The Contribution of Turbulent Active Galactic Nucleus Coronae to the Diffuse Neutrino Flux - Damiano F. G. Fiorillo; Luca Comisso; Enrico Peretti; Maria Petropoulou; Lorenzo Sironi (The Astrophysical Journal)
Active galactic nuclei (AGN) can accelerate protons to energies of ∼10–100 TeV, with secondary production of high-energy neutrinos. If the acceleration is driven by magnetized turbulence, the main properties of the resulting proton and neutrino spectra can be deduced based on insights from particle-in-cell simulations of magnetized turbulence. We have previously shown that these properties are consistent with the TeV neutrino signal observed from the nearby active galaxy NGC 1068. In this work, we extend this result to a population study. We show that the produced neutrino flux depends mainly on the energetics of the corona—the relative fractions of X-ray, magnetic, and nonthermal proton energy—and on the spectral energy distribution of the AGN. We find that coronae with similar properties can explain neutrinos from the candidate AGN for which IceCube has reported an excess, albeit less significant than NGC 1068. Building on this framework, we show how the neutrino signal evolves with AGN luminosity, and use this AGN sequence to predict the diffuse neutrino flux from the extragalactic population, showing that it can account for the diffuse neutrino signal observed by IceCube in the ∼1–100 TeV energy range.